1996
DOI: 10.1074/jbc.271.26.15815
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Transcription Factors Are Required for Activation of Human Interleukin 9 Gene in T Cells

Abstract: The genetic elements and regulatory mechanisms responsible for human interleukin 9 (IL-9) gene expression in a human T cell leukemia virus type I-transformed human T cell line, C5MJ2, were investigated. We demonstrated that IL-9 gene expression is controlled, at least in part, by transcriptional activation. Transient expression of the luciferase reporter gene linked to serially deleted sequences of the 5'-flanking region of the IL-9 gene has revealed several positive and negative regulatory elements involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 46 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…NF-B has also been implicated in IL-9 expression in mouse macrophage cells upon LPS stimulation (46). Also, binding of NF-B to the human IL-9 promoter in T cells has been demonstrated (24,47). However, the role of NF-B in regulating IL-9 expression in mouse Th9 cell is still unknown.…”
Section: Il-9 Regulates Diverse Inflammatory Immune Responsesmentioning
confidence: 99%
“…NF-B has also been implicated in IL-9 expression in mouse macrophage cells upon LPS stimulation (46). Also, binding of NF-B to the human IL-9 promoter in T cells has been demonstrated (24,47). However, the role of NF-B in regulating IL-9 expression in mouse Th9 cell is still unknown.…”
Section: Il-9 Regulates Diverse Inflammatory Immune Responsesmentioning
confidence: 99%
“…virus type I, an NF-B site at Ϫ59 to Ϫ50 was shown to be involved in basal and PHA-induced expression of the IL-9 gene (45). Using the TRANSFAC database (www.transfac.gbf-braunschweig.de), we identified three potential binding sites for NF-B within the murine IL-9 promoter, termed NF-B1-3.…”
Section: The Il-9 Promoter Comprises Three Active Binding Sites For Nf-bmentioning
confidence: 99%
“…Within this region, an NF-ĸB site and its adjacent 20-bp upstream sequence were demonstrated to play a critical role for the IL-9 promoter activity. DNA-protein binding studies indicated that NF-ĸB, c-Jun and potentially new proteins (around 35 kD) can bind to this important sequence [7]. Therefore it seems that the cooperation of different transcription factors is essential for IL-9 gene expression.…”
Section: Structure and Genomic Architecture Of Il-9 And Its Receptormentioning
confidence: 99%
“…In human T cell leukemia virus type I-transformed human T cells, C5MJ2, a proximal region of the IL-9 promoter (34 bp, between –46 and –80) was found to be the minimum sequence for basal and inducible expression of the IL-9 gene [7]. Within this region, an NF-ĸB site and its adjacent 20-bp upstream sequence were demonstrated to play a critical role for the IL-9 promoter activity.…”
Section: Structure and Genomic Architecture Of Il-9 And Its Receptormentioning
confidence: 99%